Genomic Characterization of Cronobacter spp. and Salmonella spp. Strains Isolated From Powdered Infant Formula in Chile - Parra-Flores, Julio; Holý, Ondřej; Acuña, Sergio; Lepuschitz, Sarah; Pietzka, Ariane; Contreras-Fernández, Alejandra; Chavarría-Sepulveda, Pamela; Cruz-Córdova, Ariadnna; Xicohtencatl-Cortes, Juan; Mancilla-Rojano, Jetsi; Castillo, Alejandro; Ruppitsch, Werner; et al. (Frontiers in Microbiology, 2022)
This study characterized five Cronobacter spp. and six Salmonella spp. strains that had been isolated from 155 samples of powdered infant formula (PIF) sold in Chile and manufactured in Chile and Mexico in 2018–2020. Two strains of Cronobacter sakazakii sequence type (ST) ST1 and ST31 (serotypes O:1 and O:2) and one strain of Cronobacter malonaticus ST60 (O:1) were identified. All Salmonella strains were identified as Salmonella Typhimurium ST19 (serotype O:4) by average nucleotide identity, ribosomal multilocus sequence typing (rMLST), and core genome MLST (cgMLST). The C. sakazakii and C. malonaticus isolates were resistant to cephalothin, whereas the Salmonella isolates were resistant to oxacillin and ampicillin. Nineteen antibiotic resistance genes were detected in the C. sakazakii and C. malonaticus isolates; the most prevalent were mcr-9.1, blaCSA, and blaCMA. In Salmonella, 30 genes encoding for aminoglycoside and cephalosporin resistance were identified, including aac(6′)-Iaa, β-lactamases ampH, ampC1, and marA. In the Cronobacter isolates, 32 virulence-associated genes were detected by WGS and clustered as flagellar proteins, outer membrane proteins, chemotaxis, hemolysins, invasion, plasminogen activator, colonization, transcriptional regulator, survival in macrophages, use of sialic acid, and toxin-antitoxin genes. In the Salmonella strains, 120 virulence associated genes were detected, adherence, magnesium uptake, resistance to antimicrobial peptides, secretion system, stress protein, toxin, resistance to complement killing, and eight pathogenicity islands. The C. sakazakii and C. malonaticus strains harbored I-E and I-F CRISPR-Cas systems and carried Col(pHHAD28) and IncFIB(pCTU1) plasmids, respectively. The Salmonella strains harbored type I-E CRISPR-Cas systems and carried IncFII(S) plasmids. The presence of C. sakazakii and Salmonella in PIF is a health risk for infants aged less than 6 months. For this reason, sanitary practices should be reinforced for its production and retail surveillance.